PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA MONOPOLI TATA SURYA TERHADAP MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR - Tresia Situmorang; Jaya Adi Putra; Gustimal Witri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Natural Science learning subject (IPA) is a science that studies the universe and its contents, events that occurred within, and complex and broad. Hence, appropriate interesting, and effective media-assisted earning models are needed to achieve students’ learning objectives and motivation. STAD as a cooperative learning model emphasizes the interactionbetween students and other students to motivate and help each other in comprehending and mastering the learning materials. The research is conducted to find out the effect of the Student Team Achievement Divisions (STAD) cooperative learning model on students' learning motivation in the classroom. The research was conducted offline. The research sample involved 60 students based on two classes at class VI of SDN 35 Pekanbaru, which consisted of 30 students in the control class taught through the conventional teaching method and 30 students in the experimental class taught through the STAD cooperative learning model associated with the solar system monopoly media. Data are obtained through pretest and posttest. The method used is a quasi-experimental research method with a Nonequivalent Control Group Design. The data are analyzed by using hypothesis testing and t-test analysis techniques. The results indicate that the hypothesis testing is a significant (2-tailed) result of 0.000. Based on the significant value < 0.05, it indicates that Ho is rejected, and Ha is accepted. Thus, it can be concluded that there is an effect of STAD cooperative learning model assisted by the solar system monopoly media on students’ learning motivation at class VI of SDN 35 Pekanbaru.